Peningkatan Aktivitas dan Prestasi Belajar pada Bidang Akuntansi dengan Penerapan Model Teams Games Tournament Kooperatif - Karina Diamanda Yuana Putri (STKIP PGRI SITUBONDO, 2023)
This study aims to increase the activity and learning achievement of Accounting class students at SMK Kharisma Nusantara Purwakarta by using the Team Games Tournament (TGT) collaborative learning model in the 2022/2023 school year. This research is a class action conducted in two periods. Data collection techniques include participant observation, tests, documentation, and field notes. The data analysis used is quantitative descriptive analysis. The results showed that applying collaborative learning Teams Games Tournament (TGT) can increase student learning activities and achievements in accounting. The average numeracy score increased from 80% in Cycle I to 81% in Cycle II. In addition, the average accounting learning outcomes in the pretest Cycle I increased from 80% to 85% in the posttest. In period II, the learning outcomes of accounting in the pretest had an average of 80 which increased to 85 in the posttest. The mastery level of accounting learning outcomes in the period I was 70%, while in period II, the mastery level of accounting learning outcomes reached 83% in the fall.